EXTRACTION OF NATURAL COLOR OF BUTTERFLY PEA (CLITORIA TERNATEA L) WITH VARIABLES pH-TEMPERATURE AND CONCENTRATION FOR FOOD COLORING - Sugiarto, Bambang; Rirung, Yustin; Ardiyani, Anita Nur; Achmad, Zubaidi (Journal TECHNO, 2022)
Anthocyanins are chemical compounds contained in a plants. Anthocyanin pigments are water soluble and have pink, red, purple, blue, and yellow colors. Anthocyanins act as a natural food coloring in the form of dry powder or concentrated liquid. The production of anthocyanins from butterfly pea as a natural dye is currently not maximized yet. The anthocyanin extraction process in this study was carried out by heating the butterfly pea using aquadest as a solvent. The purpose of this study is to find the optimum conditions for extracting anthocyanins from butterfly pea, to learn the effect of temperature and pH on the absorbance and color values of the butterfly pea extract with distilled water, as well as its application as a natural dye in food. In this study, it was found out that the optimum concentration was obtained at a ratio of 15 grams:500 ml (weight of butterfly pea:solvent volume) at pH 4. This proves that the concentration will increase along with the increase in the absorbance value. The optimum concentration value occurs at a temperature of 60°C. While the lowest transmittance value was obtained in the sample with a ratio of 15 grams: 500 ml (weight of telang flower: volume of solvent) at pH 4 and a temperature of 60°C. This proves that the transmittance value is inversely proportional to the concentration value. The butterfly pea extract that obtained at pH 4 produced a bluish purple color, pH 5 produced a purplish blue color, pH 6 produced a light blue color, pH 7 produces a blue color, pH 8 produces a bluish green color, and pH 9 produces a green color.